Influence of Teachers’ Action and Views on Post-Early Grade Learners’ Decision to Sign up for Practically Based Vocations and Careers in Madina Municipality in Ghana - Otu, William (International Journal of Educational Practices and Engineering(IJEPE), 2025)
Background: The nature and status of influence on the career decisions of young people can be described as non-static and varied. The depth of such influence depends, in part, on the environment, whether geographic or community. Although career choice is a critical aspect of life, young people remain susceptible to influences of various kinds. Objective: To explore the degree of influence exerted by teachers (educational coaches, learning instructors, and educational facilitators) on the decision making of youth over the age of thirteen regarding enrollment in vocational careers. Method: A twenty-item questionnaire was administered to a sample of three hundred and eighty-four (384) post-initial grade students, composed of one hundred and ninety-two (192) males and one hundred and ninety-two (192) females. The analysis was conducted using IBM SPSS software. Results: The results show that teachers' actions and opinions greatly influence young people's decision to enroll in practical careers and vocations. Conclusions: Teachers' influence represents a significant factor in the vocational orientation of young people, especially regarding the choice of practical and technical careers.